A RARE CASE OF TURNER MIMICKER - Choo, Min Jing; Wong, Liang Wei (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Primary amenorrhea and delayed puberty are frequently encountered in primary care, prompting suspicion of Turner syndrome, especially in cases with short stature. This case underscores the importance of considering Swyer syndrome even when significant growth impairment is present. CASE A 28-year-old phenotypic female, born of a non-consanguineous union, presented with primary amenorrhea and a short stature of 1.31 meters. Physical examination revealed absent secondary sexual characteristics (Tanner stage 1). External genitalia were unambiguously female. Bone age assessment identified significant delay, corresponding to a 15-year-old. The hormonal evaluation showed hypergonadotropic hypogonadism. Thyroid function and insulin growth factor-1 levels were normal. Pelvic MRI demonstrated an atrophic uterus, absent fallopian tubes and ovaries. Karyotype analysis confirmed a 46, XY genotype, consistent with Swyer syndrome. Following pubertal induction for 3 months, she developed regular menstruation and progression to Tanner stage 3. Swyer syndrome is a rare disorder of sex development featuring female phenotype, hypergonadotropic hypogonadism and streak gonads. While 15–20% of cases result from SRY gene mutations impairing testis-determining factor function, other genes have also been implicated. Swyer syndrome classically causes tall stature from estrogen-deficient delayed epiphyseal fusion. However, our case exhibited profound short stature and severely delayed bone age, explained by the complete prepubertal estrogen deprivation abolishing both growth spurt and fusion. Additional factors, like SHOX gene variations, may have contributed to her growth impairment. Diagnostic complexity arose from initial Turner syndrome overlap; however, the absence of other Turner stigmata and 46, XY karyotype confirmed Swyer syndrome. This emphasises karyotyping’s diagnostic importance in primary amenorrhea with hypergonadotropic hypogonadism, regardless of phenotype. Hormone replacement therapy remains crucial for puberty induction, bone health and cardiovascular protection. CONCLUSION Swyer syndrome may mimic Turner syndrome in cases of primary amenorrhea with short stature. Accurate diagnosis requires comprehensive hormonal, imaging and genetic evaluation beyond clinical phenotype alone.